Pengaruh Pelatihan dan Kepuasan Kompensasi Terhadap Kinerja Karyawan - Dahri, Iftikhor; Putra, Purnama (At-Tamwil: Journal of Islamic Economics and Finance, 2024)
The purpose of the study was to analyze the effect of training and compensation on employee performance at BPR Syariah Patriot Bekasi Bank. The research design that the author uses in this research is quantitative research multiple linear regression two predicators where the research is aimed at knowing the effect of training and compensation on employee performance. The data collection technique used a questionnaire to 15 respondents in the form of BPRS Patriot Bekasi employees with data analysis using multiple linear regression. The results showed that training and compensation had a positive and significant effect simultaneously and partially on the performance of BPRS Patriot Bekasi employees. This shows that training has a positive and significant impact on employee performance. Employees who receive adequate training tend to have better knowledge and skills, so that they can be applied directly to work. The combination of good training and competitive compensation creates optimal conditions for employees to contribute maximally to company performance.